PENERAPAN SISTEM PENGELOLAAN KEUANGAN PENDIDIKAN YANG TRANSPARAN DAN AKUNTABEL DI INDONESIA - Norsyifa; Suraijiah (Program Studi Manajemen Pendidikan Islam, 2024)
An efficient, transparent and accountable education financial management system is crucial to achieving the goals of national education in Indonesia, as stipulated in the Law of the Republic of Indonesia No. 20/2003 on the National Education System. Good financial management will ensure the targeted allocation of funds to improve the quality of education and prevent budget misuse that could be detrimental to the sustainability of education programs. Although Indonesia continues to increase its education budget, various problems related to financial management, such as inappropriate fund distribution procedures and ineffective supervision, remain a major challenge. This study aims to analyze the implementation of a transparent and accountable education financial management system in Indonesia and explore the challenges and solutions to improve financial management in the future. Using a qualitative approach and literature review, this research examines the basic concepts of education financial management, the importance of transparency and accountability, government regulations related to education budgets, and the challenges faced in implementing a transparent and accountable system. he results show that despite efforts to improve transparency and accountability, there are still various obstacles, such as limited human resource capacity and infrastructure that support effective financial management. Therefore, it is necessary to increase human resource capacity, implement information technology and improve regulations to improve the education financial management system in Indonesia.